Faktor-Faktor Pendukung Dan Penghambat Pengembangan Di Kawasan Wisata Pantai Gunung Payung Desa Kutuh, Badung,Bali - Maretha, Yohana; Sunarta, I Nyoman (JURNAL DESTINASI PARIWISATA; Vol 12 No 2 (2024): VOL 12, NO 2 (2024): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2024.v12.i02.p21, 2024)
This research is motivated by supporting and inhibiting factors for development in the Gunung Payung Beach area, Kutuh Badung Village, Bali. Gunung Payung Beach is one of the popular tourist attractions that offers beautiful natural beauty and is considered to have implications that lead to increased economic prosperity, culture and environmental sustainability. This research was conducted using qualitative descriptive data and used qualitative descriptive analysis obtained from observations, interviews, literature studies and documentation. Likewise, the technique for determining informants used was a purposive sampling technique. The research results show that the Gunung Payung beach in Kutuh Badung village, Bali, is well prepared in preparing a destination which can be seen from the tourism component. The attractions, accessibility and amenities of this beach are very easy to access and offers many accommodation and transportation options. Other facilities include parking, toilets, direction signs and restaurants. It offers stunning views, unique beaches and tranquility as well as cheap entrance tickets. The supporting factor for development in the Gunung Payung Beach area is the existence of important internal factors that make a major contribution to the development of the area. Support and collaboration between community members played a major role in the success of establishing this tourist destination. There are no specific factors inhibiting development in the Gunung Payung Beach area, Kutuh Badung village, Bali, but the construction costs are due to the fact that it was used for other purposes during the Covid-19 pandemic. Gunung Payung Beach, Kutuh Village, Badung, Bali can be concluded as a sustainable tourist destination, where there is still a development process every year to develop the area into an established destination. Keywords: Development, Tourism Areas, Tourism Actors